O agendamento de notícias sobre violência doméstica e familiar no Estado do Tocantins - Souza, Natália Rezende de (Universidade Federal do Tocantins, 2020)
Violence (BERNASKI; SOCHODOLAK, 2016), Journalism and Domestic Violence (TRAQUINA, 2005) and Scheduling Theory (MCCOMBS, 2009). The study analyzed 37 news published in vehicles between June and September 2019 based on parameters of a quantitative and qualitative research (BAUER; GASKELL, 2002). The categories of analysis used in the study were: a) types of violence; b) degree of proximity or kinship with the aggressor; c) age of the victim; d) reference to children of the victim; e) scope of the agenda; f) visual aids; and g) types of sources. The research pointed out that the thematization in the state of Tocantins is used in a shallow way, not having a positive inclination for the propitiation of change in the victims' life and that little reinforces the social role of Journalism to inform and sensitize society about the consequences of domestic and family violence. The theme is still shyly conveyed and physical violence is the majority in the news. Crimes are committed against women under the age of 20 and there is an extreme inclination to rape vulnerable people. Crimes are committed by aggressors close to the victim, and the stories are short and without relevant data on the profile of the victims and their aggressors. Sources are rarely used and official and institutional sources prevail. Most of the photos are illustrative or of the weapons used in the crimes, except when they have images of the aggressors mostly turned on their backs and the use of audiovisual is still rare. The scope of the agenda consisted of the Araguaína and Porto Nacional microregions.